Translating Jane Austen's Pride and Prejudice with a Commentary - Suhail, Sahar Abdulrahman Ahmed et al. (University of Science and Technology, Sana'a, Faculty of Humanities and Social Sciences, Translation Program, 2023)
This study offers a translation to the simplified version of Jane Austen's Pride and Prejudice. It also sheds light on the challenges that we, the researchers, have faced while translating this simplified novel. These challenges are related to culture, style, structure, etc at different levels viz. word, sentence, phrase and paragraph. Moreover, the most important strategies applied by the translator researchers to deal with these challenges are discussed . In other words, a translation commentary is provided to justify the use of different strategies and lexical choices to render this novel into Arabic. The most frequently used strategies are as follows literal translation, idiomatic translation, transposition, insertion, modulation, cultural substitution, paraphrasing and transliteration. However, literal translation prevails over the other strategies to give Arabic readers a chance to be exposed to the ST culture and sometimes it serves the context well.